Exploration of the Potential of Local Plants of Melastoma malabatchricum Fruit for Food Fortification: Potential of Local Plants of M. malabatchricum Fruit for Food Fortification - fathul zannah; Kamaliah; Pramudiyanti; Ayatusaadah; Nurul Hadayati (Journal of Tropical Life Science, 2022)
Endurance can be increased by maintaining nutritional intake, one of which is by consuming local plants such as Melastoma malabatchricum  Fruit. This study aims to explore the nutritional content of Melastoma malabatchricum  fresh fruit, flour and processed products from the flour. This research was conducted at the Baristand Laboratory of the Banjar Baru Industrial Center, South Kalimantan. The results showed that flour and processed products from Melastoma malabatchricum  flour had higher nutritional content than fresh Melastoma malabatchricum  fruit. Nutritional content of Melastoma malabatchricum  flour are cal, ca, Fe, Water, Ash, Fat, Protein and Carbohydrate. These results indicate that Melastoma malabatchricum  has the potential to be developed as an ingredient for food fortification.